2007
DOI: 10.1590/s1676-26492007000200005
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features and surgical outcome of patients with indolent brain tumors and epilepsy

Abstract: INTRODUCTION: In this study the authors review the outcomes of 22 patients with medically refractory epilepsy and slow growth brain tumors. OBJECTIVES: Evaluate the clinical, electrophysiological, operative, and histopathological features. PATIENTS AND RESULTS: The majority of the tumors were located in the temporal lobe (n = 20) and involved the cortical gray matter. The most frequent tumors were gangliogliomas (n = 9), astrocytomas grade I and II (n = 6), dysembryoplastic neuroepithelial tumors (n = 5) and g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Two of the best predictors of freedom from post-operative seizures include a duration of less than one year since the onset of epilepsy and gross total surgical resection [15,16]. Tumor histopathology plays a significant role in predicting freedom from seizures after epilepsy surgery; however, there is no consensus among researchers regarding this issue [17,18]. This study retrospectively investigated different types of tumor-related epilepsy and their outcomes in the first year after epilepsy surgery.…”
Section: Open Access Journal Of Neurology and Neurosurgerymentioning
confidence: 99%
See 1 more Smart Citation
“…Two of the best predictors of freedom from post-operative seizures include a duration of less than one year since the onset of epilepsy and gross total surgical resection [15,16]. Tumor histopathology plays a significant role in predicting freedom from seizures after epilepsy surgery; however, there is no consensus among researchers regarding this issue [17,18]. This study retrospectively investigated different types of tumor-related epilepsy and their outcomes in the first year after epilepsy surgery.…”
Section: Open Access Journal Of Neurology and Neurosurgerymentioning
confidence: 99%
“…Despite the abundance of knowledge regarding surgical management of resistant forms of epilepsy, including those associated with brain tumors, especially of the low-grade type, prospective studies regarding the medical treatment of epilepsy in this type of patient are scarce [11]. Reportedly, resection of the epileptogenic zone due to the development of brain tumors lead to freedom from or significant control of seizures in 70-90% of patients [12,13]. Furthermore,…”
Section: Introductionmentioning
confidence: 99%
“…[19] Reportedly, resection of the epileptogenic zone may lead to freedom from or signi cant control of seizures in 70-90% of patients. [20,21] Furthermore, tumor type, seizure severity, early surgical intervention, frequency during the preoperative stage, histopathology of the tumors, and the extension of surgical resection to include peritumoral tissues are, reportedly, the factors that increase the likelihood of freedom from seizures postoperatively. [22] Two of the best predictors of freedom from seizures post-operation include a duration of less than 1 year since the onset of epilepsy and gross total surgical resection.…”
Section: Introductionmentioning
confidence: 99%
“…[23,24] Some recent studies have suggested that tumor histopathology plays a signi cant role in predicting freedom from seizures post epilepsy surgery; however, there is no consensus among researchers regarding this issue. [25,26] In this study we retrospectively looked for different brain tumors and their one-year post epilepsy surgery outcome.…”
Section: Introductionmentioning
confidence: 99%